2011
DOI: 10.1007/s13277-011-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of G6PD is associated with poor clinical outcome in gastric cancer

Abstract: This study aims to investigate the expression and significance of glucose-6-phosphate dehydrogenase (G6PD) in human gastric cancer progression and prognosis. Using immunohistochemistry and real-time RT-PCR assay, we identified abnormally elevated expression of G6PD in gastric cancer tissues compared to paired normal stomach mucosa tissues in 24 patients (p < 0.05). In order to investigate the correlations between G6PD and the clinicopathological features of gastric cancer, the expression of G6PD in 167 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 28 publications
5
80
1
Order By: Relevance
“…When we look from a global viewpoint, we can see that gastric cancer is the fourth most common malignant tumour and the second most common cause of cancer-associated death, accounting for a guessed 1.066.543 new cases and 800.230 deaths annually. Despite advances in surgery and chemotherapy, the prognosis of gastric cancer is poor, with an estimated relative 5-year survival proportion of 10-20% in USA and European countries 3,4 . Glutathione S-transferases are the member of detoxification enzyme family and play a vital role in drug resistance in various diseases 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…When we look from a global viewpoint, we can see that gastric cancer is the fourth most common malignant tumour and the second most common cause of cancer-associated death, accounting for a guessed 1.066.543 new cases and 800.230 deaths annually. Despite advances in surgery and chemotherapy, the prognosis of gastric cancer is poor, with an estimated relative 5-year survival proportion of 10-20% in USA and European countries 3,4 . Glutathione S-transferases are the member of detoxification enzyme family and play a vital role in drug resistance in various diseases 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, G6PDH is characterized by hemolytic anemia under certain conditions and can be accompanied by chronic granulomatous disease [2,6]. Over-expression of G6PDH in Drosophila prolongs lifespan [33], while in humans such over-expression can be deleterious and favor carcinogenesis [28,52,76]. Abnormalities in regulation of G6PDH activity may lead to increased lipid biosynthesis and obesity [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies suggest an important role of G6PD in the pathology of various human diseases such as heart failure, type 2 diabetes, hypertension, 4 and cancer. 3,5 In the context of cancer research, glucose metabolism has been of interest for more than 80 years because of initial observations that cancer cells take up high amounts of glucose and produce high amounts of lactate. 6 Because lactate production is pronounced even under aerobic conditions, a high aerobic glycolytic rate was associated with cancer cell metabolism, which is known as the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by the fact that mammary carcinoma cells present an increased glucose flux through the PPP in vitro. 10 Moreover, G6PD activity is increased in tumor tissues compared with normal cells, 5,11 and silencing G6PD in tumor cells results in decreased proliferation and enhanced apoptosis in vitro. 12 Very recently, it was shown that the tumor suppressor p53 regulates the PPP activity by binding to and suppressing G6PD, highlighting the impact of G6PD in cancer cells.…”
Section: Introductionmentioning
confidence: 99%